Multi-platform imaging of lithospheric magnetic anomalies - Rajaram, M. (My University, 2003)
The paper highlights the results of the long wavelength magnetic anomalies over the Indian subcontinent as evidenced by data collected from the satellites, available aero and marine magnetic data and ground magnetic data collected at coarse intervals by the Indian institute of Geomagnetism. The paper brings out the intricacies involved in the analysis of magnetic data and brings to focus its utility in the understanding of the evolution of the Indian lithosphere. Chanockitic lithologies contribute significantly to long wavelength magnetic anomalies. The paper lays emphasis on the requirement of ground truths to constrain geopotential data.
Keywords: Aeromagnetic data; Indian lithosphere; Magnetic field; Lithosphere